2009
DOI: 10.1055/s-0029-1237361
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance in Depressed Inpatients, under Treatment with Mirtazapine and in Healthy Controls

Abstract: Impaired glucose tolerance and diabetes have been associated with depression, and antidepressant treatment is assumed to improve impaired glucose tolerance. However, antidepressant treatment is also considered as a risk factor for the development of diabetes. Reports about glucose tolerance under antidepressant treatment frequently lack appropriate control groups. We conducted the oral glucose tolerance test (OGTT) in 10 healthy controls selected from an epidemiological sample with a negative lifetime history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“…However, diabetes and “pre-diabetes” (impaired glucose tolerance and impaired fasting glucose) are diagnosed only by measured hyperglycemia (American Diabetes Association, 2013). Of note, some depressed individuals manifest insulin resistance (Nathan et al, 1981; Menna-Perper et al, 1984; Winokur et al, 1988; Okamura et al, 2000; Hennings et al, 2010) which improves with depression treatment (Nathan et al, 1981; Okamura et al, 2000; Hennings et al, 2010; Mueller et al, 1969; Weber-Hamann et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…However, diabetes and “pre-diabetes” (impaired glucose tolerance and impaired fasting glucose) are diagnosed only by measured hyperglycemia (American Diabetes Association, 2013). Of note, some depressed individuals manifest insulin resistance (Nathan et al, 1981; Menna-Perper et al, 1984; Winokur et al, 1988; Okamura et al, 2000; Hennings et al, 2010) which improves with depression treatment (Nathan et al, 1981; Okamura et al, 2000; Hennings et al, 2010; Mueller et al, 1969; Weber-Hamann et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…About 7.8 % of the US population in 2007 ( American Diabetes Association, 2010 ) and about 200 million people worldwide ( Wild et al, 2004 ) suff ered from diabetes in 2000. Although the direction of the association and possible reasons and mechanisms remain unclear so far ( Hennings et al, 2010, Weber et al, 2000, there is evidence that depression is a relevant comorbidity in diabetic subjects. In addition, there is suffi cient evidence for an association between diabetes and depression.…”
Section: Introduction ▼mentioning
confidence: 99%
“…The cross-sectional design of this study cannot show cause/effect between elevated fasting blood glucose and depressive symptoms. It may be notable, however, that several previous studies have suggested that depressed patients experience improved glucose metabolism after treatment with antidepressants as well as cognitive behavioral therapy [2123]. …”
Section: Discussionmentioning
confidence: 99%